Reactive local navigation - Castro, D. (2013)
In this paper a reactive local navigation system is presented, for an autonomous non-holonomic mobile robot navigating in dynamic environments. The reactive navigation system integrates a obstacle detection method [3] and a new reactive collision avoidance method. The sensory perception is based in a laser range finder (LRF) system. Simulation results are presented to verify the effectiveness of the proposed local navigation system in unknown environments with multiple moving objects. The comparison of results are shown, between two different approaches, a Velocity Obstacle (VO) approach and our own, based in the Dynamic Window (DW) concept.